Is chirp more effective than click and tone-burst during oVEMP test? (Annals of Medical Research, 2021)
Aim: We aimed to show the effectivity of chirp stimulus and to compare with tone-burst and click stimulus during ocular VEMP (oVEMP) and also to exhibit same stimulation response pattern in utricle as seen in cochlea. Material and Methods: A total of 85 healthy volunteers without any vestibular and otologic disease history were enrolled in this study. Three different types of air conduction stimuli (tone-burst, click and chirp) were used for the oVEMP test. N1, P1 latencies, N1P1 amplitudes and asymmetry ratios were investigated for each stimulus type according to age subgroups and sex.Results: The ratio of presence of oVEMP response was found to be 94.1%, 82.1% and 98.8% with tone-burst, click and chirp stimuli respectively. The latencies were significantly shorter in chirp stimulus with respect to others in both ears. The amplitudes were also significantly larger in chirp stimulus with respect to other in both ears. According to analysis of N1P1 asymmetry ratios, N1 and P1 latency asymmetry, there were no statistically significant difference in these values within each stimulus types.Conclusion: oVEMP is more practical, easier, faster and less invasive method. oVEMP results with chirp stimulus have shorter latency and higher amplitude and more clear waveform morphology with higher ratio of response when compared to click and tone-burst stimulus. As a result, chirp is a reliable and suitable stimulus type for oVEMP analysis. In the light of these unique results with chirp stimulus, utricular hair cells may have similar frequency specific tonotopic organization as seen in cochlea.